1975
DOI: 10.1111/1523-1747.ep12598093
|View full text |Cite
|
Sign up to set email alerts
|

Desmosomes, Filaments, And Keratohyaline Granules: Their Role In The Stabilization And Keratinization of The Epidermis

Abstract: Components of desmosomes, filaments, and keratohyaline granules were studied by electron microscope and biochemical methods to clarify their role in the stabilization and keratinization of the epidermis. Isolated desmosomes are composed of 76% protein, 17% carbohydrate, and 10% lipid. The bulk of protein consists of a "spectrin"-like fibrous protein, presumably present in the plaque, and of glycoproteins in the desmosomal interspace. The main component of filaments, prekeratin, is a low-sulfur alpha-protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 31 publications
3
54
0
1
Order By: Relevance
“…4a) and show a variety of bizarre branchings and interconnections. They resemble the arrays described by Brecher in Pt K1 cells (8) and also the tonofilaments and prekeratin fibrils present in various epithelia, especially epidermis (11,12,18,21). The filaments in Pt K2 cells differ from microfilaments not only by their greater diameter, but also in other properties.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…4a) and show a variety of bizarre branchings and interconnections. They resemble the arrays described by Brecher in Pt K1 cells (8) and also the tonofilaments and prekeratin fibrils present in various epithelia, especially epidermis (11,12,18,21). The filaments in Pt K2 cells differ from microfilaments not only by their greater diameter, but also in other properties.…”
Section: Resultssupporting
confidence: 72%
“…They further exhibit a conspicuous tendency to aggregate laterally and form ;tudies in indirect imheavily stained spicule-or rod-like bundles in which the indi-16), H17 serum gives vidual fibrous constituents are no longer distinguishable ( Fig. n the cytoplasm and 4), a situation which closely resembles the fibril-keratohyalin serum is used on 3T3 granule associations during early steps of keratinization procemid, colchicine, or cesses (11,12,18,21). Like the fibrous bundles of keratinizing )und the nucleus are epithelia, the 7-to 10-nm filaments of Pt K2 cells also show ese bundles increases frequent associations with clusters of ribosomes, probably higher concentrations polyribosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material isolated consists almost exclusively of tangles of tonofilaments, many of which are connected to residual structures of the desmosomal plaques and of the terminal web and are enriched in cytokeratins. We have not yet been able to identify possible constituent proteins of the desmosomal plaque proper, similar to the relatively large polypeptides described for isolated desmosomes from bovine muzzle epidermis by Skerrow and Matoltsy (10,60,61) . The relationship of the proteins found in high salt-extracted apical tonofilaments from intestinal cells to the ethylenediamine-extractable protein associated with tonofilaments of rat epidermis (62) also remains an open question .…”
Section: Discussionmentioning
confidence: 73%
“…However, Parakkal and Matoltsy (1968), Wong (1974) and Matoltsy (1975) showed that keratohyaline granules were amorphous and round matrixes with high density. Since we were not able to find such structures in the peridermal layers, the peridermal granules might be different from keratohyaline granules.…”
Section: Discussionmentioning
confidence: 94%